KONFLIK BATIN TOKOH AKIRA SAKAMOTO DALAM MANGA FAMILY COMPLEX KARYA MIKIYO TSUDA - Hariyanti, Ayuk Silvia; Rahmah, Yuliani; Fadli, Zaki Ainul (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
This research discusses about Akira’s personality conflict in Japanese comic’s Family Complex by Mikiyo Tsuda. Akira is the second son of the Sakamoto Family and he lived with his Family in harmony. Sakamoto Family are japanese family who livedsame with another japanese family.The different is, all of the member from Sakamoto Family has a perfect face, except Akira. That different makes Akira feel uncomfortable if he gather round with his family. The writter thought, what happened with Akira can be happenedtoo with another child in the world.The purpose of this research areto answer the problem about personality conflict of Akira Sakamoto based on Family Complex’s manga by Mikiyo Tsuda. The methods which used in this research are structural method and Sigmund Freud’s personality method. The result shows that most of Akira’s personality influenced with his superego. Akira’s low self-confident make him involvedthe conflict with his self. For example, when Akira going out with his family for dinner. His “Id” want to stay at home because he feel so uncomfortable with his family, but in the other side, his “superego” want to going outbecause he won’t make his family sad. The winner from the conflict between Akira’s “Id” and “superego” is “superego”. So, Akira’s “ego” doing the “superego” which is going out with his family for dinner.